Feasibility of e-booklet learning media on the concept of human reproductive system - Amalia Kusuma Devi; Noorhidayati Noorhidayati; Hardiansyah Hardiansyah (STKIP Persada Khatulistiwa Sintang, 2021)
Educators are the major players in the teaching process to enhance the accomplishment of student learning results. Biology subject, mainly the concept of Human Reproductive System, necessitates media relevant to learning objectives, student conditions, and technology development. Hopefully, learning media can assist the learning process by being packaged attractively to reach learning standards. In this case, the selected form of learning media is E-Booklet. This study aims to describe the feasibility of E-Booklet Learning Media in Concept Human Reproductive Systems. The research technique involves the step-by-step study and development utilizing a 4D model: 1) define, 2) design, 3) develop, and 4) disseminate. The feasibility of the E-Booklet has indicated the results of testing by 3 (three) experts using a feasibility instrument. The Human Reproductive System E-Booklet test shows that the results are very feasible (4.49) utilized as a biology learning medium. The dissemination of E-booklets is done online through posters that contain links and barcodes of E-booklets that can be accessed via the internet.